Ecological Analysis of Maternity Care in Indonesia in 2018 - Dinnya Yesica Tandy; Hario Megatsari; Agung Dwi Laksono; Mursyidul Ibad (Institute of Medico-legal Publications Pvt Ltd, 2021)
Policies that encourage maternity care to health care facilities are an important effort to reduce maternalmortality rates. This study aims to analyze the factors related to maternity care coverage in Indonesia. Theecological analysis was conducted using secondary data from the Ministry of Health of the Republic ofIndonesia report in 2018. All provinces were taken as samples. In addition to coverage of childbirth in healthcare facilities as the dependent variable, there were 6 independent variables analyzed in this study, namelypercentage of poor families, a ratio of primary health care/100,000 population, a ratio of hospital/100,000population, a ratio of gynecologist/100,000 population, a ratio of midwife/100,000 population, andcoverage of health insurance ownership. Data were analyzed using cross-tabulation. The results show thepercentage of poor families tends to have a negative relationship with maternity care coverage. Besides,four other variables were found to tend to have a positive relationship with maternity care coverage, namelythe ratio of primary health care/100,000 population, the ratio of hospital/100,000 population, the ratio ofgynecologist/100,000 population, and coverage of health insurance ownership. Meanwhile, the ratio of themidwife/100,000 population was found to have no relationship with maternity care coverage in Indonesia. Itwas concluded that 5 variables show the tendency of the relationship with maternity care coverage in healthcare facilities in Indonesia.